Level of and factors associated with optimal uptake of intermittent preventive treatment for malaria in pregnancy at private-not-for-profit health facilities in Kasese district. - Julius Mutoro; Justus Barageine Kafunjo; Freddy Eric-Kitutu; Joan Kalyango; Iving Mumbere; Nathan Nshakira (Public Library of Science (PLoS), 2024)
Malaria in pregnancy poses a high risk of poor maternal and neonatal outcomes and WHO recommends IPTp. However, its uptake has remained sub-optimal among mothers who attend antenatal care at private-not-for-profit health facilities. This study determined the level of and factors associated with uptake Intermittent preventive treatment of malaria for pregnant women (IPTp) at private-not-for-profit (PNFP) health facilities in Kasese District, Uganda. This was a cross-sectional study involving 396 postpartum mothers in the postnatal wards of 8 PNFP health facilities in Kasese district was conducted in September 2022. One hospital and 2 Health Centre IVs were purposively selected and 5 Health Centre IIIs selected randomly. Mothers were consecutively selected and interviewer administered semi-structured questionnaires were used to collect the data. Data were entered in epi-data version 3.1, cleaned and analyzed using STATA version 14. Data were adjusted for clustering & modified poison regression was used to determine associations of the factors and the outcome. From the analysis, level of optimal uptake of IPTp was 51.5% CI = (46.6-56.4). Being married (aPR = 1.35, 95% CI = 1.06-1.7, p = 0.014), attending ANC more than 4 Visits (aPR = 1.29, 95%CI = 1.09-1.54, p<0.001) positively influence optimal uptake while not taking IPTp at recommended time intervals (aPR = 0.49, 95%CI = 0.39-0.62 p<0.001) and mothers paying for IPTp drugs themselves (aPR = 0.74, 95%CI = 0.57-0.97, p = 0.031) negatively influence optimal uptake. This moderate uptake of IPTp among pregnant mothers suggests insufficient protection of pregnant mothers against malaria. Efforts to improve Antenatal care attendance, taking IPTp at recommended time intervals, not paying for ITPp drugs and encouraging marriages should be intensified.